Avaliação da Política de Cotas da UFC: Desvelando os Desafios da Educação Superior Inclusiva - Barbosa, Milena Teixeira (2020)
The main objective of this dissertation is to evaluate the program of vacancy reserves for People with Disabilities (PwD) for access to higher education, regulated by Law No. 12.711 / 2012 – also known as “Quota Law” – which was amended by Law No. 13.409 / 2016, taking as reference the experience of the Federal University of Ceara (UFC). Based on the premise that the adoption of quotas for PwD launches new challenges for the University, through this evaluation, it was sought to discuss and understand the senses and meanings attributed to the favor of expanding access and permanence in higher education for PwD, under the perception of managers, teachers and quota students with disabilities involved. The evaluative perspective chosen was the In-depth Evaluation (Rodrigues, 2008, 2011). Therefore, it was a research with a qualitative approach in which bibliographic, documentary and field research techniques were used, through semi-structured interviews that were submitted to content analysis. It was concluded that the program represents a great achievement in promoting the inclusion of PwD, but it is still very recent and allowed by complex and challenging obstacles. It is expected, from this evaluative investigation, to enable reflection on the quota policy for PwD, unveiling its intentionalities, main advances and challenges, seeking to contribute, from a theoretical perspective and with the production of new indicators, to overcome their fragilities and for the effective attainment of their political objectives.